Geolocating Dive Recorder (GDR) processing code - Schmidt, Annie; Lisovski, Simeon; Lescroël, Amélie; Ballard, Grant (Zenodo, 2023)
Contains code for processing raw data from Geolocating Dive Recorders deployed on Adelie penguins on Ross Island (2016-2018) Code folder contains R scripts for processing raw pressure data into dive statistics (dive data processing) and processing light data into locations (geoloc code) Project was funded by National Science Foundation awards 1543498, 1543541, 1543459 and NASA award Award No. 80NSSC19K0189. Please contact Annie Schmidt aschmidt@pointblue.org or Grant Ballard gballard@pointblue.org with questions. If you use this software, please cite it using the metadata from this file.